STRATEGI PEMASARAN DALAM MENINGKATKAN MINAT PEMBELI - Mufidatul Himmah (IZZI: Jurnal Ekonomi Islam, 2023)
The purpose of this study was to determine the strategy used at the Toko Rakhato increase sales in this business unit.  The type of data source used in this study is primary where this primary data is obtained from the results of interviews conducted with the owner of the Counter Toko Rakha, the object in this study is the application of strategies to the Counter Toko Rakha, which aims to find out how the process progresses.  and the implementation of the strategy implemented by Toko Rakha.  Toko Rakhahas carried out various good strategies, also has a principle which does not want to be outdone by existing business units, so the strategies that are carried out are also very rarely carried out by other business units, and because this strategy makes Toko Rakha - Najah Store is growing and is in great demand by consumers. Strategy is a set of related activity plans to find out consumer needs and develop, promote, and set appropriate prices for products or services to achieve customer satisfaction and earn profits.  The marketing strategy includes target consumers, advertising, promotion mix, and media determination.